In vitro antioxidant activities and gas-chromatography-mass spectrometry (GC-MS) analysis of antioxidant active fractions of Dialium indum var. indum L. fruit - Osman, Muhammad Faris (2017)
The fruit of Dialium indum var. indum L. or locally known as ‘keranji’ from the family Fabaceae is one of the wild fruits of Malaysia. Measurement of in vitro antioxidant capacity and activity of various crude extracts and fractions of the fruit parts using total phenolic content (TPC), cupric ion reducing antioxidant capacity (CUPRAC), DPPH radical scavenging, and linoleic acid peroxidation inhibition assays revealed that exocarp dichloromethane fraction (EDF) and seed methanol fraction (SMF) were the most antioxidant active fractions. GC-MS analysis of trimethylsilyl (TMS)-derivatized EDF and SMF further revealed different area percentage of saccharides, fatty acids, amino acids, sesquiterpenes, polyols, dicarboxylic acids, and phenolics in their total ion current (TIC) chromatograms. Presence of eight known antioxidant phenolics namely vanillic acid, syringic acid, ferulic acid, isoferulic acid, vanillin, syringic aldehyde, p-hydroxybenzaldehyde, and coniferyl aldehyde were detected only in EDF while six antioxidant amino acids namely pyroglutamic acid, glutamic acid, phenylalanine, proline, serine, and threonine were detected only in SMF. Using GC-MS analysis, this study showed the distinctive classes of phytochemical constituents in the exocarp and seed of D. indum var. indum L. fruit, which collectively contributed to their good in vitro antioxidant capacities and activities.